TGFam‐Finder: a novel solution for target‐gene family annotation in plants. Issue 5 (5th June 2020) - Kim, Seungill; Cheong, Kyeongchae; Park, Jieun; Kim, Myung‐Shin; Kim, Jihyun; Seo, Min‐Ki; Chae, Geun Young; Jang, Min Jeong; Mang, Hyunggon; Kwon, Sun‐Ho; Kim, Yong‐Min; Koo, Namjin; et al.
Summary: Whole‐genome annotation error that omits essential protein‐coding genes hinders further research. We developed Target Gene Family Finder (TGFam‐Finder ), an alternative tool for the structural annotation of protein‐coding genes containing target domain(s) of interest in plant genomes. TGFam‐Finder took considerably reduced annotation run‐time and improved accuracy compared to conventional annotation tools. Large‐scale re‐annotation of 50 plant genomes identified an average of 150, 166 and 86 additional far‐red‐impaired response 1, nucleotide‐binding and leucine‐rich‐repeat, and cytochrome P450 genes, respectively, that were missed in previous annotations. We detected significantly higher number of translated genes in the new annotations using mass spectrometry data from seven plant species compared to previous annotations. TGFam‐Finder along with the new gene models can provide an optimized platform for comprehensive functional, comparative, and evolutionary studies in plants.